2016
DOI: 10.1002/gps.4641
|View full text |Cite
|
Sign up to set email alerts
|

The cost of diagnosis and early support in patients with cognitive decline

Abstract: ObjectiveRecent research indicates considerable heterogeneity in the provision of memory assessment services (MAS). However, little is known on the extent of variation in the costs of the services MAS provide. We investigated the costs of supporting patients with suspected dementia, including assessment and support over the following six months. MethodsClinic costs were estimated on the basis of an organisational survey reporting staff roll, grade and activities. Costs of primary health and social care were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Full details of the resource use and costing approach are reported elsewhere (16). Briefly, total MAS costs included diagnostic services, and half (6 months) of the annual MAS costs with interventions and follow up care.…”
Section: Resource Use and Costsmentioning
confidence: 99%
“…Full details of the resource use and costing approach are reported elsewhere (16). Briefly, total MAS costs included diagnostic services, and half (6 months) of the annual MAS costs with interventions and follow up care.…”
Section: Resource Use and Costsmentioning
confidence: 99%
“…We conducted a longitudinal study that followed up 1318 patients referred to 69 MAS in England . In previous papers, we reported HRQL, costs, and cost‐effectiveness between first assessment and 6 months. The studies reported that MAS improved patient's HRQL, according to both disease‐specific and generic HRQL instruments, irrespective of the severity of peoples' cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported that MAS improved patient's HRQL, according to both disease‐specific and generic HRQL instruments, irrespective of the severity of peoples' cognitive impairment. While there was little variation in outcome between MAS, there was considerable variation in costs and cost‐effectiveness . However, the sustainability of such changes over a longer time period is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of a large random sample of MASs in England conducted in 2015 (Chrysanthaki et al, ) revealed considerable variation in both their structural characteristics (such as staffing levels, skill mix and provision of post‐diagnostic support) and their processes (such as waiting times, length of appointments and frequency of follow‐up). Given the wide differences in costs per patient that result from such variation (Pennington et al, in press), it is important to know if such characteristics are associated with patient outcomes (Figure ).…”
Section: Introductionmentioning
confidence: 99%